ANALISIS PENYAJIAN LAPORAN KEUANGAN PADA AKUN UTANG DAGANG OLEH KAP HELIANTONO & REKAN CABANG SEMARANG (STUDI KASUS PERUSDA FARMASI) - Lestari, Titin; Dewantara, Ghiyats Furqan (Journal Accounting International Mount Hope, 2025)
The need for precise and accurate financial information is very important to support managerial decision making. Accurate financial statements will provide a clear picture of the company's financial position. This study aims to analyze the presentation of financial statements on accounts payable in Perusda Farmasi audited by KAP Heliantono & Partners Semarang Branch. The method used is descriptive qualitative research, with primary data obtained through interviews and observations, as well as secondary data from related documents. The results of the analysis showed that there were recording errors in the financial statements that were not in accordance with the supporting documents, which had a significant impact on the company's income statement. The efforts made by the auditor to overcome this problem are by tracing the transactions that occur in the accounts payable account and adjusting the accounts payable account of Perusda Farmasi